2018
DOI: 10.1029/2017jd027502
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties Caused by Major Meteorological Analysis Data Sets in Simulating Air Quality Over India

Abstract: Many places in India suffer from severe air pollution. Regional air quality simulations are essential to develop effective strategies for improving air quality, considering the nonlinear relationships between ambient pollutants and their precursor emissions. Meteorological fields used in simulations are derived from regional meteorological models with analysis data sets as inputs. This study reveals that two major analysis data sets provided by the National Centers for Environmental Prediction and the European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…The model results driven by NCEP under-predict RH by 20-40%, despite an underestimation in high RH regime (RH>50%) can also be observed in the results driven by ECMWF. These findings are consistent with a recent study (Chatani and Sharma, 2018), which shows the WRF-Chem driven by ECMWF can reproduce much better meteorological conditions compared with observations over India than the driven by NCEP. They also reported that this is a general situation over the whole year (2010) of India and North Pakistan simulation, but the pre-monsoon (April-May) possibly experiences the largest underestimation of RH by S4 more than 20% over Delhi in the results driven by NCEP.…”
Section: S2 Comparison Between Simulations Driven By Ecmwf and Ncep supporting
confidence: 93%
“…The model results driven by NCEP under-predict RH by 20-40%, despite an underestimation in high RH regime (RH>50%) can also be observed in the results driven by ECMWF. These findings are consistent with a recent study (Chatani and Sharma, 2018), which shows the WRF-Chem driven by ECMWF can reproduce much better meteorological conditions compared with observations over India than the driven by NCEP. They also reported that this is a general situation over the whole year (2010) of India and North Pakistan simulation, but the pre-monsoon (April-May) possibly experiences the largest underestimation of RH by S4 more than 20% over Delhi in the results driven by NCEP.…”
Section: S2 Comparison Between Simulations Driven By Ecmwf and Ncep supporting
confidence: 93%
“…The initial and boundary conditions for chemical species are provided from MOZART-4 global results (https://www.acom.ucar.edu/wrf-chem/mozart.shtml). Our baseline simulation is driven by European Centre for Medium-Range Weather Forecasts (ECMWF) meteorological data, as we find that 135 this reproduces regional meteorology better than that from the National Centers for Environmental Prediction (NCEP) over India, consistent with a recent study (Chatani and Sharma, 2018) (Sahu et al, 2011), and is therefore closely related to traffic emissions, and we combine 155 this into the traffic sector for our study.…”
supporting
confidence: 66%
“…This has recently been reported in a number of Asian megacities, e.g. Shanghai (Silver et al, 2018), Beijing (Wu et al, 2015;Liu et al, 2017;Chen et al, 2018) and Guangzhou (Liu et al, 2013). Delhi and coastal cities in India, which are known to be VOC-limited (Sharma et al, 2017), may face increased O 3 as a side effect of emission controls focused on PM 2.5 .…”
Section: Introductionmentioning
confidence: 83%
“…Delhi and coastal cities in India, which are known to be VOC-limited (Sharma et al, 2017), may face increased O 3 as a side effect of emission controls focused on PM 2.5 . Therefore, studies of mitigation strategies that target both PM 2.5 and O 3 are urgently needed (Chen et al, 2018), particularly as urban air pollution in India has been much less well studied than in many other countries.…”
Section: Introductionmentioning
confidence: 99%